PENGARUH ARUS KAS, MODAL KERJA, DAN PERPUTARAN AKTIVA TETAP TERHADAP TINGKAT SOLVABILITAS - Rivanda Arli Wijaya; Sri Ayem (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study is to describe the influence of Cash Flow, Working Capital and Fixed Asset Turnover on the level of solvency, simultaneously or partially. The object of research is Cash Flow, Working Capital, Fixed Asset Turnover, and Solvency, while the subject of the research was PT Matahari Putra Prima Tbk. Methods of data collection using the documentation, while data analysis techniques using multiple linear regression. The regression equation in this study are: Y= 1,198 + 4,132-13 X1 â€“ 4,478E-13 X2 + 0,014 X3. Cash Flow, Working Capital and Fixed Asset Turnover has the effect of 18.4% to level of solvency.Keyword:Â Cash Flow, Working Capital, Fixed Asset Turnover